Activity Pattern of Self Care in Patients with Diabetes Mellitus Type II - Mulya, Adelse Prima; Kosassy, Siti Mutia (Fundamental and Management Nursing Journal, 2020)
Introduction: Diabetes Mellitus (DM) is a chronic disease that cannot be cured, only everyone can control and be aware of. The purpose of this study was to describe selfcare activities in type II DM patients.Method: The design of this study was descriptive, with a patient population of type II diabetes mellitus. This research was conducted in the Sukajadi Bandung Community Health Center Work Area. The sampling technique used the Cohen sample size with the number of samples based on the sample size of 67 respondents. Data collection using the SDSCA instrument. This study used univariate analysis including demographic characteristics of type II DM patients and self-care activity. Result: The highest mean value of self-care activity was on the diet variable, and the lowest was on the blood sugar monitoring variable. That is, in this study DM patients tend to pay attention to diet rather than monitoring blood levels.Conclusion: From the whole series of self-care activities, DM patients tend to pay attention to diet patterns rather than other activities such as; monitoring blood levels, physical activity, foot care, medication and smoking. Comprehensive self-care activities will help improve the quality of DM patient's intake. Involvement across sectors, communities and families is an important part of increasing awareness of DM patients to increase their self-care activities in order to reduce the risk of severity of DM disease.